2020
DOI: 10.1002/fsn3.1441
|View full text |Cite
|
Sign up to set email alerts
|

Orostachys japonicus extract inhibits the lipopolysaccharide‐induced pro‐inflammatory factors by suppression of transcription factors

Abstract: Orostachys japonicus (O. japonicus) was extracted with ethanol (EtOH) and sequentially separated with organic solvents, including n‐hexane (Hex), dichloromethane (DCM), ethyl acetate (EtOAc), n‐butanol (BuOH), and water (H2O). All the fractions were confirmed for anti‐inflammatory activity in an inflammatory condition. The DCM fraction showed the highest anti‐inflammatory ability. Here, we examined the effect of DCM fraction and investigated the intracellular signaling pathways in LPS‐stimulated RAW 264.7 macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The dichloromethane extract (DCM) of O. japonicus component significantly inhibited the mRNA levels of pro-inflammatory mediators and cytokines in LPS-stimulated cells. The anti-inflammatory effects of DCM have been reported to inhibit inflammatory responses through the inhibition of NF-κB activation and MAPK signaling, which is regulated by proteins upstream of MAPK and PI3K/Akt signaling pathways [ 3 , 4 , 41 ]. The 1,4,6-β-Glcp glycosidic bond in OFP might be an important mechanism contributing to the immunostimulatory activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dichloromethane extract (DCM) of O. japonicus component significantly inhibited the mRNA levels of pro-inflammatory mediators and cytokines in LPS-stimulated cells. The anti-inflammatory effects of DCM have been reported to inhibit inflammatory responses through the inhibition of NF-κB activation and MAPK signaling, which is regulated by proteins upstream of MAPK and PI3K/Akt signaling pathways [ 3 , 4 , 41 ]. The 1,4,6-β-Glcp glycosidic bond in OFP might be an important mechanism contributing to the immunostimulatory activity.…”
Section: Resultsmentioning
confidence: 99%
“…The Orostachys genera, containing twelve species, is widely distributed in China, Korea, Mongolia, and Russia. O. Japonicus is the most studied plant of Orostachys spp., and it is well known for its immunomodulatory, anticancer, anti-inflammatory, and antioxidant activities [ 1 , 2 , 3 , 4 ]. In comparison to O. japonicus , Orostachys fimbriata has been used as a medicinal plant in China for more than 1000 years.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of AP-1 Pathway. AP-1 is a pivotal factor in the regulation of inflammation by producing proinflammatory mediators and cytokines such as iNOS, COX-2, IL-1β, and IL-6 [15]. Phosphorylation of c-Jun, which is a member of the AP-1 family, induces translation of gene, and produces protein for TNF-α [16].…”
Section: Anti-inflammatory Activity Of the Pse Throughmentioning
confidence: 99%
“…Still, its clearance capacity may wear off, causing prolonged or excessive inflammatory response [ 125 , 126 ]. Lee, 2020 [ 127 ] reported that AP-1 and IRF-3 in the cell nucleus are considered pivotal factors in regulating inflammation by producing pro-inflammatory mediators and cytokines. The bovine endometrium was reported to express a wide range of immune factors, including interleukin [IL] 1β-2, -6, -8, and -10, and tumor necrosis factors.…”
Section: Inflammatory Cytokines and Chemokines In Bovine Endometritismentioning
confidence: 99%